(untitled) (Revista Electrónica REDINE, 2020)
This essay intends to reflect on the teaching task from the perspective of the constituent interests of knowledge. In order to systematize a theoretical base for the scientific community of the Center for Research in Context and Socio-Educational Praxis (CICPSE), specifically the researchers of the Teaching Research and Teacher Training Line who develop studies on this subject. That is, those who intend to understand and interpret at different levels and modalities of the Venezuelan Educational System, how the teacher articulates his actions by virtue of promoting the social development of a country from the formation of the new generations. In summary, teaching is a dynamic and recursive activity aimed at reflecting on the educational fact, by virtue of reconceptualizing and resignifying the educational, curricular and pedagogical actions, undertaken in educational practice to lay the foundations of a country’s social development.